Romania: Ten Years of EU Membership - Gábor Hunya (Romanian Journal of European Affairs)
By joining the European Union as of 1st of January 2007, Romania made use of a window of opportunity which may not have been open later. In the ten years that followed, advantages and challenges of the membership have in part been overshadowed by the impact of the global financial crisis. The country went through a boom-bust-boom economic cycle. The swing from overheating to depression and back again to overheating has been amplified by pro-cyclical economic policy. Romania has been a selective policy taker in the EU often delaying fiscal and legal actions resulting in lost benefits. By reviewing the current political uncertainties in Europe, the conclusion emerges that more effective governance and more active foreign policy is necessary under the current Europe-wide orientation loss. The country may need to develop a mobilising strategy and policy beyond the direct benefits provided by the EU, one that also contributes to the success of the European integration.